A reflexivização no PB e a decomposição semântica de predicados - Luisa Andrade Gomes Godoy (2012)
This work aims to analyze the phenomenon of reflexivization in Brazilian Portuguese (BP) and to use what is called predicate decomposition, as a more explicit representation of linguistic meaning. Reflexivization is analyzed from the standpoint of lexical semantics, that is, we observehow BP verbs behave when reflexivized. We offer a description of verbal classes in BP in terms of predicate decomposition, proposing semantic representations for both the verbal class and the reflexive form of that verbal class. This empirical analysis allows us to define reflexivity and topoint out the restrictions for reflexivization. Reflexivity occurs when there are two arguments with identical denotative value in a predicate decomposition structure, regardless of which thematic role they bear (that is, regardless of the nature of the relation between the argument and the predicate it saturates). As for the restrictions for reflexivization, we divide them in two types. The first type of restrictions is some requirements for the arguments of a verb, so that verb can be reflexivized: there must be two arguments and they must denote animate individuals. In the empirical survey mentioned, we dealt only with verbs that fulfilled those requirements, so the impossibility of reflexivizing a verb class could be attributed to the lexical semantic features it bears. These lexical semantic restrictions are the restrictions of the second type. We propose that these restrictions are not specific to reflexivization, but are instead violations of some general semantic principles. So, reflexivization seems to occur in a productive way within the BP verbal lexicon, because it is not restricted to a single class. The empirical survey also allowed us toinvestigate the difference between strictu sensu reflexives and middles. We propose that both forms present the idea of reflexivity in their meaning, but they differ as to how the two subevents that compose the meaning of the verb are related. Strictu sensu reflexive presents a causality relation between the subevents of the verb, while middle presents a temporal overlapping relation between the verb`s subevents. Apart from the empirical survey, we develop a discussion aboutreflexivization regarding its relation to grammar. After evaluating proposals in the literature, we understand reflexivization is more adequately explained as a syntactic composition, not as a lexical operation. We then propose a means of adapting the representations given to a more traditional model of grammar. The structures representing verbal classes are lexical representations and the structures representing reflexive forms are representations of (theinterpretation of) sentences. Apart contributing for the understanding of reflexivization, we can point out that this work also contributes for the description of BP, because of the empirical work with the verbal classes, and for the semantic language of predicate decomposition.